Triggering Factors of Budgetary Slack by Managers: A Literature Review - Andi Muhammad Dzul Fahmi Ismail; Serly; Maghfiratul Alyannisa; Febrina Nur Ramadhani (Program Studi Akuntansi Fakultas Ekonomi dan BisnisUniversitas Nusa Nipa, 2026)
Budgetary slack remains a critical issue in managerial accounting because it distorts financial information, leads to inefficient resource allocation, and weakens organizational accountability. Although empirical research on its triggering factors has grown rapidly, the findings remain fragmented and scattered across diverse contexts, leaving limited comprehensive synthesis. This study aims to identify, classify, and synthesize the triggering factors of budgetary slack by managers into an integrated conceptual map. The research employs a systematic literature review with content analysis of 21 relevant empirical articles published between 2017 and 2025, sourced from the Google Scholar, Garuda, and SINTA databases. The findings identify nineteen triggering factors classified into two interacting categories: organizational and systemic factors that create opportunities for slack, explained through Agency Theory; and individual and motivational factors that drive managerial behavior, explained through Expectancy Theory. Notably, several formal control mechanisms such as accountability, incentive schemes, and job involvement consistently show no significant effect. The study contributes an integrated conceptual model and offers practical guidance for designing more effective control systems to mitigate slack.